Politics, Local Governments, and Sharia By-Laws in Indonesia: Revisiting A Common Assumption (UINSI Samarinda, 2018)
After the fall of Suharto regime, some local governments in Indonesia have adopted Shari’a by-laws. Several studies suggest that this adoption of Shari’a by-laws was influenced mostly by the political motives of the local elites. They used such by-laws as a strategy to gain political supports from Muslim voters. They also used the by-laws to facilitate bribery and electoral corruption using social and religious instruments and to distract people’s attention from ongoing corruption. Although it confirms the political motives behind the adoption of the Shari’a by-laws, this paper suggests that such political motives may not the only factors leading to the introduction of Shari’a by-laws. Based on the study of the political and religious backgrounds of the district heads, who were elected in the local elections between 2008 and 2013, in the six major provinces, this paper indicates that political motives do not play alone. The district heads’ religious backgrounds can be the other important factors contributing to the adoption of Shari’a by-laws by some local governments in Indonesia.Keywords: Shari’a by-laws, politics, local governments, Indonesia.